INSTITUTIONAL-STRUCTURAL DYNAMICS OF THE SPHERE OF DEBT SERVICES IN POST-CRISIS PERIOD - A. V. Osipov (Russian Journal of Economics and Law)
The article is devoted to the dynamics of institutional changes in the sphere of debt services in the Russian Federation. The role of consumer crediting in the mechanism of problem debts distribution in post-crisis economy. The weaknesses of institutional environment regulating the debt relations are stated. The author describes the Russian features of collectors’ activity and its potential for solving the problem of households’ non-payments.